Evaluation of intramuscular sodium nitroprusside injection to improve oxygenation in white-tailed deer (Odocoileus virginianus) anesthetized with medetomidine–alfaxalone–azaperone. (January 2021) - Lakhdhir, Sarifa; Caulkett, Nigel; Duke-Novakovski, Tanya; Woodbury, Murray; Boysen, Søren
Abstract: Objective: In ungulates, α2 -adrenergic agonists can decrease oxygenation possibly through alteration of pulmonary perfusion. Sodium nitroprusside can decrease pulmonary vascular resistance (PVR) and increase cardiac output ( Q ˙ t ) through vasodilation. The objective was to determine if sodium nitroprusside would improve pulmonary perfusion and attenuate the increased alveolar–arterial (a –a) gradient resulting from medetomidine–azaperone–alfaxalone (MAA) administration. Study design: Prospective, randomized, crossover study with a 2 week rest period. Animals: A group of eight adult female captive white-tailed deer ( Odocoileus virginianus ). Methods: Deer were administered MAA intramuscularly (IM), and auricular artery and pulmonary artery balloon catheters were placed. Deer spontaneously breathed air. Saline or sodium nitroprusside (0.07 mg kg –1 ) were administered IM 40 minutes after MAA injection. Heart rate (HR), mean arterial pressure (MAP), mean pulmonary arterial pressure (MPAP), pulmonary artery occlusion pressure (PAOP), right atrial pressure (RAP), Q ˙ t, arterial pH, PaCO2 and PaO2 were obtained immediately before nitroprusside injection (baseline) and 5, 10 and 15 minutes afterwards. Mixed venous blood samples were obtained at baseline and at 5 minutes. Systemic vascular resistance (SVR), PVR, intrapulmonary shunt fraction ( Q ˙ s / Q ˙ t ), a –a gradient, oxygen delivery ( D ˙ O2 ) and oxygen extraction ratio (O2 ER) were calculated. Statistical analysis was performed with repeated measures analysis of variance with correction factors. A p value < 0.05 was considered significant. Results: With nitroprusside, MAP, MPAP, PAOP, RAP, SVR and O2 ER significantly decreased and HR, Q ˙ t and D ˙ O2 increased compared with baseline and between treatments. There was a significant decrease in PVR and a –a gradient and increase in PaO2 compared with baseline and saline treatment. Changes were not sustained. Conclusions and clinical relevance: Nitroprusside temporarily changed hemodynamic variables, increased PaO2 and decreased a –a gradient. Nitroprusside possibly led to better pulmonary perfusion of ventilated alveoli. However, IM nitroprusside at this dose is not recommended because of severe systemic hypotension and short action.